Contribuição ao Conhecimento da Distribuição Geográfica do Tatu-de-Rabo-Mole-Grande Cabassous tatouay no Brasil: Revisão, Status e Comentários sobre a Espécie - Ubaid, Flavio Kulaif; Siqueira Mendoca, Leonardo; Maffei, Fabio (Conservation International, 2010)
The greater naked-tailed armadillo Cabassous tatouay is one of the least-known armadillo species. Field records are rare, if not controversial, and only few specimens exist in scientific collections in Brazil. This species is listed in the Brazilian Red List of Threatened Species as well as in six official Brazilian state Red Lists. Fieldwork was performed between 2005 and 2008 to monitor wildlife in the central-western region of São Paulo State. Cabassous tatouay was registered in three opportunities, in the municipalities of Agudos, Borebi and Avare, and ecological and morphometrical data were registered. Although this species tolerates altered habitats, the scarce field records may be related to its habits and have led to the lack of basic information on greater naked-tailed armadillos. This communication provides important ecological and biogeographical information about C. tatouay.
Geographical distribution of the greater naked-tailed armadillo Cabassous tatouay from Brazil: revision, status and comments on the species